Patient-ly Waiting: A Review of Patient-Centered Access to Inflammatory Bowel Disease Care in Canada. Issue 1 (1st March 2018) - Mathias, Holly; van Zanten, Sander Veldhuyzen; Kits, Olga; Heisler, Courtney; Jones, Jennifer
Abstract: Canada has one of the highest prevalence estimates of inflammatory bowel disease (IBD) in the world. Like other chronic illnesses, access to specialist care is required for disease management. Traditionally, access to care is evaluated through wait times (actual access); however, new patient-oriented definitions of access (perceived access) highlight other equally important facets of access to care (e.g., appropriateness). Aim: How does access to gastroenterology speciality care influence disease-related outcomes for IBD patients in Canada? A comprehensive literature review was undertaken. Cochrane, PubMed and CINHAL databases were searched for peer-reviewed English language articles published between 2006 and 2016. Inclusion/exclusion criteria focussed on access to IBD care in Canada. Included articles were classified using Levesque et al.'s patient-centered access framework (e.g., affordability, accessibility, appropriateness, acceptability, availability and accommodation). Eight articles were found, including six which addressed patient-centered access. Most of the articles addressed issues of availability (e.g., wait times), appropriateness and affordability. Only one article addressed approachability and acceptability of IBD care. All articles emphasized a need for greater patient-centered measures (e.g., multidisciplinary clinics) with a goal to improve patient access and, ultimately, patient outcomes. Understanding patient-centered access to IBD care is important for managing IBD and improving patient outcomes. Literature examining access to gastroenterology services is limited. Increased investment in patient-oriented research should be made to better understand the relationship between access to specialist care and patient outcomes.